Design of Explanatory Text Learning Devices for Class VII Indonesian Language Subjects in Middle School - Ogi Hendrayana (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the planning stage, the teacher must design learning devices. The learning device in this study is the Learning Implementation Plan (RPP) which contains competencies, objectives, materials, strategies, media, learning scenarios, and assessments. The formulation of the problem of this research, namely: How is the design of explanatory text learning tools for class VII Indonesian Middle School subjects and how is the implementation of the design of explanatory text learning tools for grade VII Middle School Indonesian subjects? This study involved expert weighers in the validation test and 35 class VII students of SMP Negeri 1 Sumber as research subjects. The stages of this research consist of designing learning tools based on the ASSURE design model. Data collection techniques through interviews and questionnaires. Data analysis techniques, namely analytic description. Based on the research results, the average validity of learning tools obtained from expert reviewers is 84.32% with a level of validity, which is quite valid or can be used, but needs minor revisions, the average student learning outcomes is 81.67, the percentage of responses teachers to the implementation of learning tools is 86.67% with a very strong relationship level, and the percentage of students' responses to the implementation of learning tools is 89.39% with a very strong relationship level. So, the designed explanatory text learning tool for Indonesian Language and Literature in SMP Class VII is quite valid and the response is very strong/good in its implementation